THE MESSAGE OF EDUCATIONAL CHARACTER WISDOM IN THE MINANGKABAU CLASSIC STORY - Abdurahman Abdurahman (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
The objective of this paper is to describe the phenomenon of cultural educational wisdom messages in the Minangkabau classic story, especially kaba stories contained in